EDUKASI PENGOLAHAN DAN PEMILAHAN SAMPAH PLASTIK GUNA PENINGKATAN EKOLITERASI ORANG TUA SISWA TK CAHYA MENTARI - Hakika, Dhias Cahya; Asih, Hayati Mukti; Biddinika, Muhammad Kunta; Yuwantina, Anissa; Safitri, Anggi; Sugianti, Ardina Fitri (Jurnal Abdi Insani, 2024)
Garbage is identified as objects or materials that are no longer deemed necessary, useful, or wanted, and are often disposed of by individuals or communities. Various sources and categories of garbage and waste exist, which, without proper management, could contaminate soil, water, and air. Implementing educational programs on waste management is crucial to boost community awareness and involvement in mitigating the detrimental effects on environmental and public health. Particularly, enhancing parental awareness of waste is essential for cultivating environmental stewardship in young children. This community service initiative aims to educate parents, especially those of students at TK Cahya Mentari in Semarang District, on the processing and sorting of primarily plastic waste to improve their eco-literacy. The program includes a series of educational and technical guidance sessions that introduce fundamental waste management principles, effective sorting techniques, and the adoption of eco-friendly practices in daily life. This intervention is intended to enable parents to incorporate these practices into domestic routines and to instil environmental consciousness in their children. This program resulted in a significant increase in knowledge, with parents’ understanding improving from 53% to 91.33%. The results from this initiative indicate that the educational efforts have successfully enhanced parental understanding of waste management, thereby contributing to the development of environmental awareness among children at TK Cahya Mentari.